The Utility of Using Preoperative MRI as a Predictor for Intraoperative Pituitary Adenoma Consistency and Surgical Resection Technique - Yun, Jonathan J.; Johans, Stephen J.; Shepherd, Daniel J.; Martin, Brendan; Joyce, Cara; Borys, Ewa; Reddy, A. Suresh; Patel, Chirag R.; Germanwala, Anand V. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective Most pituitary adenomas are of soft consistency and can be resected during surgery with routine suction instruments. However, fibrous adenomas may require more aggressive techniques. The ability to predict consistency on magnetic resonance imaging (MRI) would improve preoperative preparation and may have implications on the extent of resection.Design A retrospective review of MRI and tumor histology of 50 consecutive patients who underwent endoscopic endonasal resection for nonfunctional adenomas was performed.Methods An intensity ratio was calculated based on quantitative MRI signal intensity of the adenoma and pons. Intraoperatively, a sequentially graded technique required for resection ranged from suction (R1) for softer tumors, curettes (R2) for tumors with intermediate consistency, and aspirators and/or other microinstruments (R3) for firmer tumors. Fibrotic content was determined from histologic collagen percentage, and rates of gross total resection (GTR) were calculated from postoperative imaging. Statistical analyses were performed to determine if resection classification could be predicted by intensity ratio or collagen percentage, calculate ratio of cut-off points for clinical use, and assess for correlation between intensity ratios and collagen percentage.Results Tumors with ratios < 1.6 on the T2-weighted coronal image and collagen content > 5.3% were likely to have required a more aggressive resection technique. Statistically significant lower rates of GTR and higher rates of perioperative complications were seen with such tumors.Conclusion Preoperative MRI analyses can be helpful but not definitive in predicting adenoma consistency. Fibrous adenomas, associated with higher collagen content, are more difficult to resect and have higher rates of subtotal resection.
Keywords: Endoscopic; pituitary adenoma; transsphenoidal; tumor consistency